Application of data acquisition and telemetry system into a solar vehicle - Taha, Z.; Passarella, R.; How, H.X.; Md Sah, J.; Ahmad, N.; Ghazilla, R.; Yap, H.J. (2010)
The Center for Product Design and Manufacturing (CPDM) of University Malaya going to take part in the World Solar Challenge (WSC) 2009. It is a biannual solar powered car race over 3021 km from Darwin to Adelaide. The aim of this project is to build a system for monitoring performance of the solar vehicle during testing and race, a data acquisition and telemetry (DaqT) system is needed. In this project, a DaqT system will be developed using National Instruments' (NI) Lab VIEW, compactRIO (cRIO) and MaxStream Xstream Radio Frequency modules. The DaqT is able to measure signals from sensors which are thermocouples, current transducers, battery storage and tachometer. Experiment is conducted to investigate the capability of the DaqT system to process signals from essential sensors, transmit data with wireless communication and data logging. The results of this project from the experiment, the DaqT manage to transmit data in open space up to 700 meters and the percentages of the error is below 5%.